2019
DOI: 10.3390/ijms20092098
|View full text |Cite
|
Sign up to set email alerts
|

Precision Revisited: Targeting Microcephaly Kinases in Brain Tumors

Abstract: Glioblastoma multiforme and medulloblastoma are the most frequent high-grade brain tumors in adults and children, respectively. Standard therapies for these cancers are mainly based on surgical resection, radiotherapy, and chemotherapy. However, intrinsic or acquired resistance to treatment occurs almost invariably in the first case, and side effects are unacceptable in the second. Therefore, the development of new, effective drugs is a very important unmet medical need. A critical requirement for developing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 157 publications
0
13
0
Order By: Relevance
“…The survival rates considerably depend on several factors including age, sex and tumor types [1,2]. The clinical management is often through surgery, radiotherapy, or chemotherapy interventions either individually or in combination [3,4]. Even though tumor resection surgery has improved overall survival rates and other related outcomes, it is not as effective as when it is combined with other available treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The survival rates considerably depend on several factors including age, sex and tumor types [1,2]. The clinical management is often through surgery, radiotherapy, or chemotherapy interventions either individually or in combination [3,4]. Even though tumor resection surgery has improved overall survival rates and other related outcomes, it is not as effective as when it is combined with other available treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that PLK4 knockdown reduces invasion, induces epithelial phenotype in breast cancer cells and plays an important role in cancer metastasis . Another study found that increase in PLK4 expression enhances the resistance of GBM cells to radiotherapy, and inhibition of PLK4 enhances the effect of temozolomide via reduction of IKBKE phosphorylation; besides, depletion of PLK4 in glioma cells using CRISPR/CAS9 significantly decreased the proliferation, viability and survival of glioma cells, increasing the susceptibility of cancer cells to DNA damage agents . Another study reported that a combination of bortezomib and PLK inhibitor showed a significantly higher anti‐tumour effect compared with bortezomib treatment alone in multiple types of head and neck cancers .…”
Section: Introductionmentioning
confidence: 99%
“…On this ground, genes mutated in primary microcephaly (MCPH) syndromes have already been proposed as possible targets for MB-directed drug development [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%